Acciones Preventivas para Evitar la Manipulación Parental, que Vulnera el Interés Superior del Niño - Segarra Cáceres, Byron Xavier (2018)
The present thesis on "Preventive actions to avoid parental manipulation that violates the best interests of the child" can be defined parental manipulation as a form of psychological abuse that is carried out by one of the parents or the adult who is in charge and care of the child, being able to be a boy, girl and adolescent in such a way that it is a problem of great magnitude that is occurring not only in Ecuador but also in some countries such as Brazil and Spain that was established in the comparative civil legislation, due to the fact that that divorces or separations by couples have been increasing, reaching the point of having some type of violence between ex-spouses either before the separation or after the same putting at risk the family disintegration especially the child who is the most vulnerable of the family because of their young age violate their integrity and their rights. Noting that parental manipulation affects psychologically creating traumas to the child when one of the parents begins to introduce completely false issues against the other parent whose purpose is detachment, hatred and parental-filial rejection, when giving this type of manipulation the child alienated will begin to project in a negative way and with aggressiveness against the father and his family likewise will begin to have social and academic problems so it can be highlighted from the legal point that is evident, when this type of abuse is given the violation to the best interest of the child contemplated in the Constitution and in the Code of Childhood and Adolescence, so according to the research work that allowed me to observe that the Code of Childhood and Adolescence does not specify any sanction to the aggressor father of this type of psychological abuse that affect children and adolescents to a large extent, due to what is observed in the cases in which custody or parental authority is determined by the legal vacuum in the face of parental manipulation or alienation, thus arriving at a reform proposal according to field research applied to legal professionals, judges and magistrates in which results could be obtained positive and favorable for my research.